How to shift to a more equitable and job‐friendly path. Issue 1 (5th August 2013) - Escudero, Verónica; Khatiwada, Sameer; Malo, Miguel Ángel
Abstract: This Chapter shows how an approach that balances macroeconomic and employment goals, while at the same time taking social impacts into account, is necessary to achieve a sustainable and inclusive recovery. Moving towards such an approach requires attention to be paid to a number of policy areas, including macroeconomic, labour market and social protection policies. In addition, this Chapter highlights a wide range of recent initiatives that have made an effort to achieve this kind of rebalancing.